2012
DOI: 10.1002/jms.2020
|View full text |Cite
|
Sign up to set email alerts
|

Validated LC–MS/MS method for quantification of agomelatine in human plasma and its application in a pharmacokinetic study

Abstract: An analytical method based on liquid-liquid extraction has been developed and validated for analysis of agomelatine in human plasma. Fluoxetine was used as an internal standard for agomelatine. A Betasil C18 (4.0 × 100 mm, 5 µm) column provided chromatographic separation of analytes followed by detection with mass spectrometry. The method involves simple isocratic chromatographic conditions and mass spectrometric detection in the positive ionization mode using an API-4000 system. The proposed method has been v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 1 publication
0
33
1
Order By: Relevance
“…Different organic solvents were investigated to extract analytes from the plasma samples. Compared with ethyl acetate which was used by the literature (Patil et al ., ), n ‐hexane–dichloromethane–2‐propanol (20:10:1, v/v/v) mixture yields better results, and was selected as the liquid–liquid extraction solvent, which considerably improved the extraction recovery of agomelatine to more than 90%. Dozens of compounds in our laboratory were evaluated for the screening of IS, and fluoxetine, clarithromycin, telmisartan and diazepan were chosen as IS candidates owing to their similar chromatographic behavior to agomalatine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different organic solvents were investigated to extract analytes from the plasma samples. Compared with ethyl acetate which was used by the literature (Patil et al ., ), n ‐hexane–dichloromethane–2‐propanol (20:10:1, v/v/v) mixture yields better results, and was selected as the liquid–liquid extraction solvent, which considerably improved the extraction recovery of agomelatine to more than 90%. Dozens of compounds in our laboratory were evaluated for the screening of IS, and fluoxetine, clarithromycin, telmisartan and diazepan were chosen as IS candidates owing to their similar chromatographic behavior to agomalatine.…”
Section: Resultsmentioning
confidence: 99%
“…The plasma concentrations of agomelatine differ greatly, so the analytical method plays an important role in the study of pharmacokinetics. To our knowledge, only one LC‐MS/MS method for the determination of agomelatine in human plasma has been published recently (Patil et al ., ), but its extraction recovery is relatively low, and the linear range and dilution factors are not adequate for our study because our preliminary test showed that the mean plasma concentrations of agomelatine in Chinese volunteers may be higher than those reported. Therefore we developed a new method with higher extraction recovery and wider determination range compared with the reported one, which was selective, sensitive, efficient and stable in analyzing plasma samples obtained from the pharmacokinetic study of agomelatine in Chinese healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…According to the available agomelatine pilot data, the sample size in the present study was estimated by referencing the literature by Chow et al 17) For determination of agomelatine in human plasma, an original LC-MS/MS method was developed and validated. Compared to the reported methods, 18,19) it was less time-consuming and had a wider range of quantification (0.05-20 ng/mL). The sampling scheme design was considered adequate for the determination of pharmacokinetic parameters with sufficient duration to fully assess the absorption and elimination phases of agomelatine.…”
Section: Discussionmentioning
confidence: 97%
“…Because of its action upon the melatonine receptors, agomelatine shows a marked improvement on sleep. Agomelatine has also proven to have anxiolytic properties and thus may prove to be very useful in the treatment of anxiety disorders [4][5].…”
Section: Introductionmentioning
confidence: 99%